Plano de segurança contra incêndio e pânico (PSCIP): estudo de caso de adaptação ao novo código em edificação construída entre os anos de 1991 e 1995 em Pato Branco, Paraná - Scarmocin, Luiza Marta (2017)
The changes that have been taking place in the fire safety legislation for buildings in the country of Brazil end up in the need of adapting existing buildings to the new ruling laws. The adaptation of existing buildings to the new legislation occurs in a different way from the implementation of the laws for new buildings since for an existing building (built before the existence of current legislation) may be encountered constructive and architectural impossibilities that require an alternative treatment. This study presents an evaluation of the fire safety measures of an existing building and adapts it to the New Fire and Panic Safety Code that came into effect in 2012 in the state of Paraná, Brazil. The adaptation was carried out by dimensioning the safety measures required and subsequent verification of its existence or not in the building. If the safety measure existed in the building it was verified its compliance with the respective Technical Procedures Standard (NPT) making adjustments if necessary. In cases where the measure did not exist in the building, its prediction was made in the Fire and Panic Safety Plan (PSCIP) of the building. It was noticed that the cases in which the adaptation to the New Code was more complicated were the ones that required adequacies of the safety measures that were already installed in the building, but were in disagreement with the provisions of the respective NPT, mainly due to limitations imposed by the construction model of the building, in addition, the adaptation of the safety measures will not always strictly follow the provisions of the NPT.